Hubungan Komunikasi Orangtua dengan Kesiapan Sekolah Anak Usia 5-6 Tahun - Rahmah; Herwina; Hasdiati, Hilda; Juniarti, Yenti (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2024)
This research aims to determine the relationship between parental communication and early childhood school readiness at Syifana Lucky Kids Kindergarten. This research is quantitative with a correlation method. This research was carried out at Syifana Lucky Kids Kindergarten Jalan Kualu/Suka Karya Panam. The time of the research was carried out from September to October 2023. The population of this research was children and their parents at Syifana Lucky Kids Kindergarten, totaling 30 children/parents, while the sampling technique used was a census sampling technique so that the research sample was 30 children/parents. The data collection techniques used were observation and questionnaires. The data analysis technique uses the product moment correlation test. The results of the research are that there is a relationship between parental communication and early childhood school readiness at Syifana Lucky Kids Kindergarten as evidenced by the r value > r table or you can also see the sig value less than 0.05 (0.005 <0.005). The conclusion is that the relationship between parental communication and children's school readiness is in the medium category and has a positive relationship.